Determinants of purchase intention of Halal packaged food among non-Muslim consumers in Thailand. (8th April 2021) - Syukur, Muhammad; Bungkilo, Dej-anan; Jongsureyapart, Chatrudee
Halal food is not specially nor exclusively prepared for Muslim consumers. It is the food for all faith, Muslim and non-Muslims. Thailand's dream to be the Halal hub in the region must start from the readiness of the country. This paper is an expanded version of the previous research which took Thai Muslim consumers as the samples. This research aims to test the determinants of purchase intention from Thai non-Muslims for Halal packaged food. Multiple regression analysis is applied to the data from 193 respondents representing all four regions in Thailand. It is found that the place, promotion, and awareness are determinants for purchase intention on Halal packaged food. By matching the result of the related research on Thai Muslims, it is concluded that place (product availability) and awareness are determinants of purchase intention of Halal packaged food among both Muslims and non-Muslim in Thailand.